Evaluation of Consumer Acceptance and Satisfaction from Solar Energy Products - Kansal, Bindiya; Pathania, Ajay Kumar (Prabandhan: Indian Journal of Management, 2016)
As one of the largest energy consuming state, Punjab is facing environmental worsening, which occurs due to excess use of non-renewable conventional sources of energy such as coal. Solar photovoltaic (PV) energy is an indefinite and clean energy with minimum harmful impact on the environment. In the present study, we designed and conducted a survey in six districts of Punjab. Based on the primary data, we utilized basic statistical methods to observe respondents’ knowledge, concerns, and attitudes towards PV adoption. The research aimed to recognize the drivers and dynamics that normally influence consumers to establish solar PV system in their homes. The results suggested that respondents’ satisfaction differed across cities, and lack of financial support by the government is the major barrier that limits diffusion of solar energy.